The effects of thermal acclimation on cardio-respiratory performance in an Antarctic fish (Notothenia coriiceps). Issue 1 (13th December 2018) - Joyce, William; Axelsson, Michael; Egginton, Stuart; Farrell, Anthony P; Crockett, Elizabeth L; O'Brien, Kristin M
Abstract : In Notothenia coriiceps, acclimation to increased temperature (5 vs. 0°C for 6.0–9.5 weeks) increased upper thermal limits of the cardiovascular system during acute heating. Whilst cardiac output increased with acute heating as a result of elevated heart rate, after chronic warming cardiac output was surprisingly increased primarily by an elevation in stroke volume. Abstract: The Southern Ocean has experienced stable, cold temperatures for over 10 million years, yet particular regions are currently undergoing rapid warming. To investigate the impacts of warming on cardiovascular oxygen transport, we compared the cardio-respiratory performance in an Antarctic notothenioid ( Notothenia coriiceps ) that was maintained at 0 or 5°C for 6.0–9.5 weeks. When compared at the fish's respective acclimation temperature, the oxygen consumption rate and cardiac output were significantly higher in 5°C-acclimated than 0°C-acclimated fish. The 2.7-fold elevation in cardiac output in 5°C-acclimated fish (17.4 vs . 6.5 ml min −1 kg −1 ) was predominantly due to a doubling of stroke volume, likely in response to increased cardiac preload, as measured by higher central venous pressure (0.15 vs . 0.08 kPa); tachycardia was minor (29.5 vs . 25.2 beats min −1 ). When fish were acutely warmed, oxygen consumption rate increased by similar amounts in 0°C- and 5°C-acclimated fish at equivalent test temperatures. In both acclimation groups, the increases in oxygen consumption rate during acute heating were supported by increased cardiac output achieved by elevating heart rate, while stroke volume changed relatively little. Cardiac output was similar between both acclimation groups until 12°C when cardiac output became significantly higher in 5°C-acclimated fish, driven largely by their higher stroke volume. Although cardiac arrhythmias developed at a similar temperature (~14.5°C) in both acclimation groups, the hearts of 5°C-acclimated fish continued to pump until significantly higher temperatures (CTmax for cardiac function 17.7 vs. 15.0°C for 0°C-acclimated fish). These results demonstrate that N. coriiceps is capable of increasing routine cardiac output during both acute and chronic warming, although the mechanisms are different (heart rate-dependent versus primarily stroke volume-dependent regulation, respectively). Cardiac performance was enhanced at higher temperatures following 5°C acclimation, suggesting cardiovascular function may not constrain the capacity of N. coriiceps to withstand a warming climate.